Utilization of Pine needles for preparation of Sheets for Application as Internal Packaging Material - Gupta, Praveen Kumar; Joshi, Gyanesh; Rana, Vikas; Rawat, Jaipal Singh; Sharma, Ashish (Indian Forester, 2020)
Chir pine scientifically known as Pinus roxburghii is one of the six pines of India and the most widely occurring specie among coniferae family. Coniferous pine trees shed pine needles as tree waste in large amount during summer season and form a thick carpet on the forest floor. These needles are rich in resin content and often cause forest fires. It is well known that burning of any biomass is the last choice for mankind until and unless it finds its suitability for formation of other goods. The present study demonstrates that pine needles can serve as a potential material for production of variety of internal packaging materials through environmental friendly and chemical free mechanical pulping process vis-a-vis providing a livelihood support to local communities.